Internalisasi Karakter melalui Model Project Citizen pada Pembelajaran Pendidikan Pancasila dan Kewarganegaraan - Surya Dharma; Rosnah Siregar (Universitas Negeri Medan, 2014)
This writing deals with developing moral values by the ‘project citizen’ through several stages of its learning. Hopefully this article could act its role in enlightening and motivating for the teachers to be able to use this model later. Starting from the idea of character building by John Dewey (1859-1952) through the flow of Progressivism. He explains that